Chasmogamy and entomophily in Burmannia disticha (Burmanniaceae) - Vislobokov, Nikolay A.; Nuraliev, Maxim S. (Frontiers in Plant Science, 2023)
Burmannia shows a set of floral traits that suggest elaborate mechanisms of animal-mediated pollen transfer. These include flower coloration, septal nectaries and a long and narrow floral chamber. The stamens are synorganized with the common style restricting the entrance to the floral chamber, sometimes forming a gynostegium. Contrary to this apparent zoophilous floral syndrome, several species of Burmannia were reported to perform self-pollination via cleistogamy. Understanding of reproductive systems in Burmannia is complicated by scarcity of available results of direct observations on pollination process. Here we present data on pollination biology of B. disticha obtained during field investigations in Vietnam followed by laboratory analyses of ecologically important floral traits and the captured flower visitors. We found that the anthetic perianth is open, i.e. the flower is chasmogamous. The flowers are visited by various Diptera, Hymenoptera, Lepidoptera and Orthoptera. Of them, the bumblebees (Bombus burmensis), a bee (Coelioxys sp.) and some lepidopterans were revealed to carry pollen of B. disticha. Based on the amount of carried pollen, insect behavior during the visits and general knowledge on biology of these insect taxa, we concluded that the bumblebees act as the principal pollinators of B. disticha, whereas the lepidopterans are considered as its possible pollinators. We compared the lengths of proboscises of the captured insects to the depth of the floral chamber, and found that only the bumblebees and lepidopterans should be able to reach the nectar. Finally, we estimated the pollen-ovule ratio of B. disticha as 6.84, which is comparable to the ratio known in autogamous angiosperms. Based on its flower organization and pollination mechanism, we consider B. disticha an entomophilous and predominantly xenogamous species. Its gynostegium is likely an adaptation for pollen transfer by insects with long proboscises. At the same time, earlier investigations together with pollen-ovule ratio indicate that B. disticha possesses a labile pollination strategy, and autogamy sometimes occurs. Since Burmannia is one of the few angiosperm genera that comprise both mycoheterotrophic (achlorophyllous) and autotrophic (green) species, our study provides important evidence for reconstructions of ecological and morphological evolutionary pathways in relation to the mode of organic nutrition.